Effect of Perceived convenience and perceived trust on Facebook marketplace patronage in Nigeria (UNIZIK Journal of Marketing, 2024)
The main objective of this study was to ascertain the effect of perceived convenience and perceived trust on Facebook Marketplace patronage in Nigeria. This cross-sectional study adopted a descriptive survey research design. The population of the study comprised users of Facebook Marketplace in Nigeria. For the sample size, a minimum of 240 respondents were selected using convenience sampling based on sample size calculations. The study's hypotheses were tested using regression analysis with SPSS Version 25.0. Findings revealed that perceived convenience had a positive and significant effect on Facebook Marketplace patronage in Nigeria. Additionally, perceived trust also had a positive and significant effect on Facebook Marketplace patronage. The study recommended that Facebook Marketplace users should increase online trust by offering various options that build confidence, such as quick and prompt product delivery, cash-on-delivery options, and maintaining honesty and transparency, to mitigate users' perceived risks.
Keywords: Perceived convenience; Patronage; Perceived trust; Technology Acceptance Model (TAM); Facebook marketplace